4.3 - Gauss Elimination with Partial Pivoting - Shams El-Din El-Fouly; Siddharth Misra (My University)
In this lesson you'll learn about how to solve a system of equations using gauss elimination with Partial Pivoting and how to develop a gauss elimination with Partial Pivoting VBA Code

This file is part of a series of video lectures for Dr. Siddharth Misra’s class, Numerical Methods for Engineering Computation, at the University of Oklahoma. The video series demonstrates how to develop numerical methods using C++, Python, and MATLAB and shows the codes and methods being developed from the scratch. Students are encouraged to develop their own codes along with the videos. The series is numbered as follows:

1.1 – 1.8

2.1 – 2.3

3.1 – 3.7

4.1 – 4.7

5.1 – 5.5

6.1 – 6.4

7.1 – 7.5

8.1 – 8.4